A study on Filipino children with maple syrup urine disease and their primary caregivers determining the relationship of children’s nutrient intake, nutritional status, leucine level, and their Primary caregivers’ nutrition knowledge, attitude, and feeding practices - Sevilla, Marife D.
Diet compliance is critical in managing maple syrup urine disease (MSUD) to prevent physiological and neurological damage. Children with MSUD are generally caregiver-reliant for their nutrition. However, there is a lack of studies investigating factors critical to diet compliance. This study examined the factors affecting the caregivers’ nutrition knowledge, attitude, and feeding practice (KAP); and its relationship to the leucine level, nutritional status, and nutrient intake of Filipino MSUD children consulting at the University of the Philippines -Philippine General Hospital (UP-PGH). A cross-sectional, sequential explanatory mixed-methods research approach, combining survey and individual in-depth interview, was used. Data were collected using questionnaires, three-day food records, and in-depth interviews. Results: There were a total of 20 caregivers and 21 MSUD children between six months to seven years old who participated in the study. Caregivers had moderately high feeding practices and nutrition knowledge scores and exhibited proper attitude to provide adequate nutritional care. Despite this, the caregivers were struggling with diet compliance. The challenges they commonly faced include feeding problems; food availability and preparation; and cost and stress related to providing care. Alternatively, facilitators in providing optimal nutritional care include motivation, coping skills, and support from family and healthcare providers. The caregivers’ nutrition knowledge was related to their attitude (p-value: 0.021) and feeding practices (p-value: 0.037). As their knowledge score increased, their attitude became more positive, as did the correctness of their feeding practices. Their knowledge and feeding practices may be related to the children’s natural protein status (p-value: 0.043 and 0.006 respectively), and their knowledge could also be related to the children’s weight-for-age (p-value: 0.036). The caregivers’ sex had a significant relationship to the children’s leucine level (p- value=0.010); children with female caregivers had lower leucine levels, by 470 μmol/L on average. Moreover, children with good leucine control belonged to higher-income households (p-value=0.049). As caregivers struggle with diet compliance, interventions to improve nutrition knowledge and feeding practices, and strategies to address the barriers are needed, with greater focus on caregiver’s sex and income. The effects of diet progression on leucine level; the caregiver’s KAP and the children’s nutrient adequacy on metabolic control; and leucine control on growth, have not been established however, likely due to the small sample size and the dietary assessment tool used. This study, with its broad scope, may serve as foundation for future research.